Graviton Signals in Central Production at the LHC - Rahul Basu; Tanumoy Mandal (Advances in High Energy Physics)
We study central production, in the inclusive case, to look for graviton signals in a large extra dimensional model using dilepton and diphoton channels. We carefully analyze signal and possible standard model background processes and study the feasibility of such new physics searches in a relatively clean environment as in central production where the proton fragments are mostly emitted in the forward direction, and there is a clear rapidity gap between them and the centrally produced system. Our analysis shows that the LHC with 14 TeV center of mass energy and 100 fb−1 (300 fb−1) of integrated luminosity can probe the effective gravity scale up to 3.6 TeV (4.4 TeV) in both the dilepton and diphoton channels.